Sustainability in Latin America and the Caribbean. An analysis of the impact of socioeconomic and political arrangements - De Araújo Ramos, Maria Regina; Sobreira de Moura, Alexandrina; Vilela Amelotti, Luiza (Estudios Internacionales, 2023)
How do socioeconomic and political arrangements relate to sustainability? Based on a sample of 24 countries in Latin America and the Caribbean, between 2011 and 2019, this study examines the hypothesis that better performance in socioeconomic and political variables is associated with higher levels of sustainability. Here, this concept is measured through the Social Progress Index (SPI) and Sustainable Development Goals (SDGs) 10, "Reduced Inequalities", and 11, "Sustainable Cities and Communities". The research design considers correlation tests, panel data regression, and an empirical description of the Chilean and Brazilian contexts. The results show that performance in the SPI and the SDG 11 is primarily associated with economic arrangements, while the SDG 10 is more closely linked to the political dynamics of the state. Furthermore, by analyzing Chile and Brazil, this study identifies that the countries also have particular effects on the indices. The conceptual impact of these results enriches socioeconomic and political interventions for sustainability and provides valuable insights for future research.